Reduction of Bladder Cancer Chemosensitivity Induced by the Effect of HOXA-AS3 as a ceRNA for miR-455-5p That Upregulates Notch1 - Chen, Dajin; Xie, Shangzhi; Wu, Ying; Cui, Yu; Cai, Ying; Lan, Lan; Yang, Hao; Chen, Jianghua; Chen, Wei (Frontiers in Oncology, 2021)
Chemoresistance is one of the main causes of recurrence in bladder cancer patients and leads to poor prognosis. Recently, long non-coding RNAs, like HOXA-AS3, have been reported to regulate chemoresistance in several types of cancer. In this study, we aimed to determine whether HOXA-AS3 can mediate cisplatin resistance in bladder cancer, and its potential mechanism of action. We determined the viability, proliferation, and apoptosis of bladder cancer cells using a CCK-8 assay, EdU staining, and flow cytometry, respectively. We used western blot to assess expression of markers of epithelial-mesenchymal transition (EMT) and Notch1. We then confirmed expression of these EMT-related markers by immunofluorescence analysis. We found hypoxia promoted resistance to cisplatin and up-regulated the level of HOXA-AS3 in BC cells. Inhibition of HOXA-AS3 enhanced hypoxia-induced cisplatin sensitivity by regulating EMT and Notch1 in BC cells. A dual-luciferase reporter assay confirmed HOXA-AS3 directly targets miR-455-5p and Notch1 was as a potential target of miRNA-455-5p. We also found the positive effect of HOXA-AS3 inhibition on cisplatin resistance and tumorigenesis was alleviated when BC cells were transfected with miR-455-5p. Finally, we showed combining HOXA-AS3 siRNA with cisplatin treatment inhibited tumorigenesis in a BALB/c nu/nu mouse model. Our findings indicate HOXA-AS3 may function as a competing endogenous RNA (ceRNA) of miR-455-5p to regulate Notch1 and plays an important role in regulating chemotherapeutic drug sensitivity in BC cells. Therefore, HOXA-AS3 may be a novel therapeutic target for treating bladder cancer.